Busca e validação da informação imagética na web - Figueiredo, Márcia Feijão de (2011)
Presents a literature review on the criteria those scientists to make judgments and validate imagetic information found during process web seeking. Describes the processes that occurred since the beginning of modern society which took place in research communities with rules and standards developed internally, the result of sub-cultures , and the images that are of interest of these users, the epistemic function. Uses inputs from the postphenomenology to explain the use of technology as a mediator for the production and access to knowledge of man. Identifies the components of seek and selection of imagetic information: the web, information seeking, the judgment criteria chosen for analysis, namely, quality of information, cognitive authority and credibility and the categories that are related literature. Analyzes the main features observed in the use of criteria for image and as Habermas understands the validation of objects symbolic of a community. Demonstrates a true story through the use of images supposedly plagiarized research in communities with different themes and how their validation differs from textual information.